(untitled) (Research, Society and Development, 2020)
Currently, the Federal Institutes have the challenge of training professionals with the profile required by the labor market; professional whose skills must surpass that of simple technicality. In this context, the technical visit has great potential for use, given that it brings students closer to the labor market. Therefore, the objective of this work was to make a diagnosis about the use of the technical visit at the Federal Institute of Education, Science and Technology of Pará - Campus Breves, as a teaching-learning tool. Methodologically, different questionnaires were applied to teachers (n = 15) and students (n = 82) addressing the topic in question. In possession of the answers, it was observed that all students positively evaluated the performance of technical visits and that they consider them important because: they relate theory to professional practice; facilitate the teaching-learning process; and help the student to understand the social environment where he is inserted. Improvements were highlighted, such as: more visits, transportation and planning. Regarding teachers, there was also a positive evaluation of the methodology, mainly in the most practical subjects. When asked about the main difficulties in carrying out the technical visit, the issues of transportation, the reconciliation of class schedules with the location of the visit and the establishment of partnerships for visits were raised.